2018
DOI: 10.5152/tud.2018.48642
|View full text |Cite
|
Sign up to set email alerts
|

Total tubeless ultra-mini supine percutaneous nephrolithotomy: A feasibility study

Abstract: Objective: The ultra-mini percutaneous nephrolithotomy (PCNL) for treating low-volume renal nephrolithiasis is being used as an alternative modality to the conventional PCNL. However its use in the supine position has been scarcely reported. Material and methods:Patients who underwent ultra-mini PCNL in the supine position within the time frame of January 2017 to July 2017 were studied. All these patients had this as their first-line treatment. The patients had calculus limited to either a single calyx or just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…A systematic review of PCNL with a tract size less than 15Fr showed an overall stone-free rate of 88.3% and no complications above Clavien grade III [7]. Previous umPCNL studies have shown average operative times ranging from 40 to 59 minutes [5, 6, 13], which is comparable to our average of 54 minutes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A systematic review of PCNL with a tract size less than 15Fr showed an overall stone-free rate of 88.3% and no complications above Clavien grade III [7]. Previous umPCNL studies have shown average operative times ranging from 40 to 59 minutes [5, 6, 13], which is comparable to our average of 54 minutes.…”
Section: Discussionsupporting
confidence: 70%
“…Gupta et al showed stone free rates of 93% in their study of tubeless umPCNL in 15 patients [6]. Agrawal et al had stone free rates of more than 99% in his study of 120 umPCNL (13).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous nephrolithotomy (PNL) is recommended as the gold standard treatment for management of stones > 20 mm in diameter by both EAU and AUA guidelines (1, 2). Also, with miniaturized instruments, stones < 20 mm can also be treated with high success and low complication rates (3). The main aim of stone surgery is to establish the stone free status due to the fact that residual fragments may result in stone related events.…”
Section: Introductionmentioning
confidence: 99%